The revolution that did not exist: the decree that could have transformed the model of financing broadcasting in Brazil - Pieranti, Octavio Penna [UNESP] (Univ Federal Sergipe, 2021)
Historically, the lack of a stable financing model is one of the problems of state and public broadcasters. This article aims to present a draft decree, formulated in 1973, and discuss its possible impacts, which could have included the establishment of a perennial source of funds for these broadcasters and their restructuring. However, this decree was never published and its content remained unknown to the public until the current research was carried out.
Keywords: Decree; State broadcasting; Public broadcasting; Financing